SYSTEM ACCEPTANCE OF STUDENT IN ENGLISH EDUCATION INSTITUTIONS YUKTI DARMA - Syapruddin Syapruddin; Irfan Irfan, Skom, MMSi (Jurnal Sistem Informasi, 2002)
an institution that has so many students, the student becomes a problem to be solved so that the necessary calculations and notes that the detailed and easily understood. New admissions system in which LPBI Yukti Darma is still produced. Especially in matters relating to the reports to the chairman of the foundation LPBI Yukti Darma. In this case it is necessary to use the computer as a tool in data processing. Â Admissions system at Darma Yukti LBPI Paradiguna admissions procedures which are carried out continuously in the quarter, revenue was comprised of students: Registration, Test, Level. The author makes admission system that can perform calculations based on the level payment amount, so that this system can be used in future to come.